What we can learn from failure: an EHR-based child protection alert system - Krawiec, Conrad (Child maltreatment, 2020)
This study aimed to evaluate the efficacy of a newly implemented Child Protection Alert System (CPAS) that utilizes triggering diagnoses to identify children who have been confirmed/strongly suspected as maltreated. We retrospectively reviewed electronic health records (EHRs) of 666 patients evaluated by our institution?s child protection team between 2009 and 2014. We examined each EHR for the presence of a pop-up alert, a persistent text-based visual alert, and diagnoses denoting child maltreatment. Diagnostic accuracy of the CPAS for child maltreatment identification was assessed. Of 323 patients for whom child maltreatment was confirmed/strongly suspected, 21.7% (70/323) had a qualifying longitudinal diagnosis listed. The pop-up alert fired in 14% of cases (45/323) with a sensitivity and specificity of 13.9% (95% CI [10.4%, 18.2%]) and 100% (95% CI [98.9%, 100.0%]), respectively. The text-based visual alert displayed in 44 of 45 cases. The CPAS is a novel simple way to support clinical decision-making to identify and protect children at risk of (re)abuse. This study highlights multiple barriers that must be overcome to effectively design and implement a CPAS to protect at-risk children.